Democratic Control of Intelligence Services: Containing Rogue Elephants - Caparini, Marina; Born, Hans (Routledge, 2007)
The events of September 11, 2001 sharply revived governmental and societal anxieties in many democratic countries concerning the threats posed by terrorism, organized crime, the proliferation and use of weapons of mass destruction, and other complex security threats. In many countries, public discourse of subjects traditionally considered part of social policy, such as immigration and asylum, have been securitized, while intelligence services have been granted greater resources and expanded powers. This comprehensive volume discusses the various challenges of establishing and maintaining accountable and democratically controlled intelligence services, drawing both from states with well-established democratic systems and those emerging from authoritarian systems and in transition towards democracy. It adopts a multidisciplinary and comparative approach, identifying good practices to make security services accountable to society and its democratic representatives. The volume will engage both academics and practitioners in the discussion of how to anchor these vital yet inherently difficult to control institutions within a firmly democratic framework. As such, it has clear relevance for these concerned with the control and oversight of intelligence and security issues in many countries.